Efficiency of topical application of regenerants and reparents containing group B vitamins in patients with post-burn symblepharon - M.B. Gushсhina; D.S. Afanasyeva (РМЖ "Клиническая офтальмология")
M.B. Gushсhina1, 2, D.S. Afanasyeva3 1NMRC "Central Research Institute of Dentistry and Orthodontic Surgery",   Moscow, Russian Federation 2Kaluga Branch of the S. Fyodorov Eye Microsurgery Federal State Institution,   Kaluga, Russian Federation 3V. P. Vykhodtsev Clinical Ophthalmological Hospital, Omsk, Russian Federation Ocular burns can lead to complex anatomic disorders and dysfunctions of the ocular surface, as well as palpebral conjunctiva and fornixes, resulting in permanent decrease in basal tear production in long-term period. Some patients need surgery to treat symblepharon and restore eyelids position, conjunctival fornixes and corneal transparency. Nonetheless, as a rule, it is impossible to resolve symptoms of dry eye due to loss of tear-producing elements. Severe decrease of tear production causes significant discomfort for such patients and enforce keratopathy even in good cosmetic result after surgery. To provide the most optimal results on the all steps of the rehabilitation for the patients with ocular burns, it is worth to add cornea reparants and artificial tears containing group B vitamins. On the basis of a clinical case was showed efficiency of topical application of regenerants and reparents containing group B vitamins in patients with post-burn symblepharon. A cornea epithelization was enhanced and improved tear film stability (tear break-up time changed from 1 to 3 seconds). Moreover, such treatment also resulted in discomfort correction and better visual acuity (change from 0.1 to 0.4). Keywords: ocular burn, artificial tears, lubricants, dexpanthenol, pantothenic acid, B5, cyanocobalamin, B12, keratopathy, dry eye syndrome. For citation: Gushсhina M.B., Afanasyeva D.S. Efficiency of topical application of regenerants and reparents containing group B vitamins in patients with post-burn symblepharon. Russian Journal of Clinical Ophthalmology. 2021;21(4):253–257 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-253-257.